Public Procurement Contract for Goods and Services Following the Presidential Decree Number 12 of 2020 on the Stipulation of the Coronavirus Disease (Covid-19) Pandemic as a National Disaster - Ninis Nugraheni; Hening Prabawa Arifanda; Alifihan Astaftiyan (Faculty of Law, Universitas Padjadjaran, 2020)
The Covid-19 Pandemic affects many sectors. Therefore, the Indonesian Government passed the Presidential Regulation Number 12 of 2020 to manage the Pandemic. Unfortunately, this regulation has evoked various interpretations on the disaster contingency as a foundation to apply force majeure condition. The Government’s policies of budget refocusing and reallocation to manage the Covid-19 Pandemic have brought significant effects on goods and services procurement contracts. This condition may lead the Government into default, and it is force majeure. Therefore, the Government is discharged from any liabilities. Consequently, it may injure contractors of procurement. This study aims to investigate the actuality of such procurement contracts following the Presidential Regulation. This study is a normative law research. Based on the Presidential Regulation, the force majeure condition is likely to be applied on procurement contracts. However, the condition does not immediately nullify or terminate the contracts. They remain legally valid and binding. In case of a condition permanently prevents debtor to fulfill obligations, contract can be terminated. In case of a condition temporarily prevents the contract’s implementation, the best solution to encourage conducive business climate is renegotiation that is legalized by contract addendum.Kontrak Pengadaan Barang dan Jasa Pasca Berlakunya Keppres No. 12 Tahun 2020 tentang Penetapan Bencana Non-Alam Penyebaran Coronavirus Disease 2019 (Covid-19) sebagai Bencana NasionalAbstrakPandemi Covid-19 berdampak pada banyak faktor dan membuat pemerintah Indonesia memberlakukan Peraturan Presiden No. 12 tahun 2020 (Perpres 12/2020). Akan tetapi, peraturan ini memunculkan banyak interpretasi tentang kemungkinan bencana untuk menjadi alasan penerapan keadaan kahar. Kebijakan pemfokusan ulang dan realokasi anggaran oleh pemerintah untuk mengatasi Covid-19 membawa dampak signifikan pada kontrak pengadaan publik. Kondisi ini dapat dikategorikan sebagai keadaan kahar, karena menyebabkan pemerintah gagal memenuhi kewajiban dalam kontrak. Oleh sebab itu, pemerintah diberhentikan dari tanggung jawab apa pun, dan hal ini dapat merugikan kontraktor. Penelitian ini bertujuan untuk menganalisa eksistensi Kontrak Pengadaan Publik setelah berlakunya Perpres 12/2020. Penelitian ini merupakan penelitian hukum normatif. Mempertimbangkan Perpres 12/2020, keadaan kahar kemungkinan akan diterapkan pada kontrak pengadaan. Namun, kondisi ini tidak serta merta membatalkan atau mengakhiri kontrak. Kontak tersebut tetap sah secara hukum dan terbatas. Hal ini harus mempertimbangkan apakah pandemi saat ini dapat mengakibatkan keadaan kahar. Dalam hal suatu kondisi yang secara permanen mencegah debitur untuk melakukan kewajibannya, kontrak akan berakhir. Dalam hal suatu kondisi yang secara sementara mencegah kontrak untuk dilaksanakan, negosiasi ulang yang ditindaklanjuti dengan adendum kontrak adalah solusi terbaik yang mendorong iklim bisnis yang kondusif.Kata kunci: Covid-19, keadaan kahar, kontrak pengadaan publik.DOI: https://doi.org/10.22304/pjih.v7n2.a5